F. OTTO, J.M. SONGEL - Frei Otto. Conversaciones con Juan Maria Songel - Colón, Alegría (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
Frei Otto, José María Songel Frei Otto. Conversaciones con Juan Maria Songel Editorial Gustavo Gili, S.L., Barcelona, 2008, 96 páginas. Idioma: castellano. Tapa blanda. 12€. ISBN 978-84-252-2205-4